Prognostic impact of immune-microenvironment in colorectal liver metastases resected after triplets plus a biologic agent: A pooled analysis of five prospective trials. (August 2020) - Moretto, Roberto; Corallo, Salvatore; Belfiore, Antonino; Rossini, Daniele; Boccaccino, Alessandra; Lonardi, Sara; Centonze, Giovanni; Morano, Federica; Germani, Marco Maria; Loupakis, Fotios; Morelli, Luca; Urbani, Lucio; et al.
Abstract: Background: Immune-contexture of tumour microenvironment (TME) influences prognosis of colorectal cancer (CRC) patients and can be altered by cytotoxic and targeted agents. Limited data are available regarding the immune-TME of CRC after treatment. Methods: An extensive immunohistochemistry evaluation of immunological parameters on tumour cells and TME of colorectal liver metastases from 106 patients who underwent secondary resection, after receiving triplets FOLFOXIRI (5-fluorouracil, oxaliplatin and irinotecan) or COI (capecitabine, oxaliplatin and irinotecan) plus bevacizumab (N = 59) or cetuximab (N = 47) in five first-line no-profit clinical trials was performed. Results: No substantial differences were reported in immunological parameters according to administered targeted agent, RAS / BRAF mutational status and histopathological or Response Evaluation Criteria in Solid Tumours response. Stromal expression of Cyclooxygenase-2 (COX-2) (p = 0.002), Human leukocyte antigen (HLA) (p = 0.003) and Programmed cell death protein 1 ( PD1) (p = 0.002) were independent prognostic factors for longer relapse-free survival (RFS) at multivariate analysis with a positive trend for post-resection overall survival (OS). Patients whose metastases expressed stromal COX-2, HLA and PD1 (inflamed-score positive) reported longer RFS (25.5 versus 9.8 months; p < 0.001) and post-resection OS (64.3 versus 37.7 months; p = 0.003) as compared with others. In addition, patients with higher expression of CD4 and CD8 T-cells in tumour core and invasive margin (CD4/CD8-score) showed a better post-resection OS (not-reached versus 41.6 months; p = 0.032). A combined score of inflamed-score and CD4/CD8-score (combo-score) showed a clear prognostic role. Conclusions: The present study emphasises the role of immune-TME as independent predictor of survival in patients resected after triplets plus biologic. Inflamed-, CD4/C8- and combo-scores should be confirmed as prognostic factors in further studies. Highlights: Immune-tumour microenvironment (TME) influences prognosis of colorectal cancer. 'Immunological scores' were built in resected colorectal liver metastasis after triplet and biologic. These 'Immunological scores' affect prognosis independently of other features. Triplet plus a biologic agent modify the immune-texture of TME. Immune-TME should be considered for trials in the post-metastasectomy setting.